2008
DOI: 10.1179/147683008x344183
|View full text |Cite
|
Sign up to set email alerts
|

Long-term consumption of sugar-rich diet decreases the effectiveness of somatodendritic serotonin-1A receptors

Abstract: 8-Hydroxy-2-(di-n-propylamino)-tetralin (8-OH-DPAT), a 5-hydroxytryptamine (5-HT)-1A selective agonist was used to investigate a possible role of somatodendritic serotonin-1A receptors in the precipitation of hyperphagia and decreases of 5-HT metabolism associated with long-term consumption of sugar rich-diet. In the first part of study, dose-related hyperphagic effects of 8-OH-DPAT were monitored in freely feeding rats. In the second part of study, rats were fed freely on a sugar-rich diet (prepared by mixing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
4
0
1
Order By: Relevance
“…Third, a study in the Netherlands showed that men who followed a high-fat, high-sugar diet for 6 weeks showed a significant decrease in level of serotonin transporter-binding in the hypothalamic region, that is, by 30%, in single photon emission computed tomography scans [ 28 ]. This decrease in serotonin level may increase the possibility of the development of anxiety and depression [ 29 ]. Fourth, the intake of sugar causes neurobiological changes in the reward system, compelling the individual to consume more sugar; it can affect negative emotional symptoms, similar to other substance-related addictive disorders [ 30 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Third, a study in the Netherlands showed that men who followed a high-fat, high-sugar diet for 6 weeks showed a significant decrease in level of serotonin transporter-binding in the hypothalamic region, that is, by 30%, in single photon emission computed tomography scans [ 28 ]. This decrease in serotonin level may increase the possibility of the development of anxiety and depression [ 29 ]. Fourth, the intake of sugar causes neurobiological changes in the reward system, compelling the individual to consume more sugar; it can affect negative emotional symptoms, similar to other substance-related addictive disorders [ 30 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In mechanistic studies with murine models, researchers showed that long-term diet rich in sugar is associated with decreased effectiveness of somatodendritic serotonin-1A receptors, which provide feedback control over the synthesis and release of serotonin (mood regulator) in the hypothalamus (32) . Hypothalamus serotonin plays an essential role in the occurrence of mental illness.…”
Section: Discussionmentioning
confidence: 99%
“…An early study [12] failed to see an effect of a high sucrose diet on the anorectic effects of the serotonin releaser dexfenfluramine in rats. Another research group, however, has observed an attenuated behavioral response, e.g., paw treading, of the direct serotonin 1-A receptor agonist 8-hydroxy-N.N-dipropyl-2-aminotetralin (8-OH-DPAT) following consumption of a diet high in sucrose in rats [13, 14], hypothesized to be related to serotonin receptor desensitization [15, 16]. …”
Section: Introductionmentioning
confidence: 99%